2023
DOI: 10.1093/burnst/tkac052
|View full text |Cite
|
Sign up to set email alerts
|

Skin 11β-hydroxysteroid dehydrogenase type 1 enzyme expression regulates burn wound healing and can be targeted to modify scar characteristics

Abstract: Background Excessive scarring and fibrosis are the most severe and common complications of burn injury. Prolonged exposure to high levels of glucocorticoids detrimentally impacts on skin, leading to skin thinning and impaired wound healing. Skin can generate active glucocorticoids locally through expression and activity of the 11β-hydroxysteroid dehydrogenase type 1 enzyme (11β-HSD1). We hypothesised that burn injury would induce 11β-HSD1 expression and local glucocorticoid metabolism, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…They also hypothesized that pharmacological manipulation of 11β‐HSD1 expression would improve aspects of residual scarring. By measuring skin 11β‐HSD1 expression in both mice and humans and using 11β‐HSD1 knockout mice to further explore the effects of 11β‐HSD1 activity on wound healing from burn trauma and quality of scar formation, Tsai et al 33 . demonstrated 11β‐HSD1 expression levels increased significantly in both mice and human skin after burn trauma ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…They also hypothesized that pharmacological manipulation of 11β‐HSD1 expression would improve aspects of residual scarring. By measuring skin 11β‐HSD1 expression in both mice and humans and using 11β‐HSD1 knockout mice to further explore the effects of 11β‐HSD1 activity on wound healing from burn trauma and quality of scar formation, Tsai et al 33 . demonstrated 11β‐HSD1 expression levels increased significantly in both mice and human skin after burn trauma ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…They cited several previous studies that reported both positive and negative findings regarding the ability of human skin to synthesize cortisol de novo, emphasizing the need to treat results from studies involving mice with caution. Furthermore, Tsai et al 33 . noted that a limitation in using a mouse model examining skin 11β‐HSD1 expression in wound healing from burn trauma is that there are differences in aspects of wound healing between mice and humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Either behavior can benefit burn wound healing depending on the severity of the injury. An over production of collagen results in disorganized scar tissue, yet collagen production is necessary for tensile strength, vascularization, and remodeling of regenerated tissue [32,33]. While collagen production in response to C2DA has not been tested previously, studies of other fatty acids have shown a concentration-dependent relationship between treatment and collagen stimulation, in that high concentrations of fatty acids can inhibit collagen deposition [34,35].…”
Section: Discussionmentioning
confidence: 99%